Liberalisme dan Hak Supir Angkot di Kota Medan - Talita Sembiring; Kania Nova Ramadhani; Al Firman; Taslima Amelia Taufik; Sri Yunita; Chandra Fhutu Neva (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2026)
This study aims to examine public minibus drivers in Medan from the perspectives of citizenship and liberalism. The research method used is descriptive qualitative with data collection techniques through in-depth interviews, participatory observation, and documentation. The results show that public minibus drivers enjoy individual freedoms, such as determining their working hours, choosing their rest times, and competing for passengers. This freedom is seen as a form of self-sovereignty in line with the principles of liberalism. However, this freedom also gives rise to contradictions, namely economic uncertainty, the burden of daily deposits, and the absence of social security and legal protection. The emergence of application-based transportation services further exacerbates the gap, as angkot drivers feel they experience inequality in terms of access to technology, regulations, and government support. This condition demonstrates the weak role of the state in guaranteeing their citizenship rights, especially those related to welfare and job protection. Thus, this study emphasizes that the principle of freedom in liberalism cannot be separated from the state's responsibility to achieve social justice. More equitable policies, technological support, and social protection for public minibus drivers are important steps to ensure that individual freedom is in line with citizenship rights.